KEWENANGAN SATUAN POLISI PAMONG PRAJA TERHADAP PERATURAN DAERAH KOTA SAMARINDA - ANGGA GALLUCI (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT This thesis entitled "AUTHORITY UNIT PRICE POLICE ON REGULATION OF THE CITY OF SAMARINDA CITY" ', with 2 (two) Principal issues are: (1) How is the Authority of Satuan Pamong Praja Police Unit on Enforcement of Local Regulation in Samarinda City (2) 2. How The Law caused when the Civil Service Police Unit does not carry out its obligations to the Regional Regulations in Samarinda City? This research is a kind of normative and empirical combined research. The result of this thesis shows that; (1) All levels of local government apparatuses, offices and agencies in the area of Samarinda City Government gradually begin to feel the importance of the existence and duties of the Civil Service Police Unit in enforcing the Local Regulations of Samarinda City. The guidance and arrangement of duties, functions and roles of the Civil Service Police Unit are well conducted, besides the Samarinda City Police Service Unit, really demonstrate its ability in upholding the discipline of Regional Regulation that actually violates the regulation of regional head. However, this is not optimal due to the many constraints faced so as to have an impact on the performance of the Civil Service Police Unit itself. (2) Legal effect of Satpol PP which does not fulfill its obligation to Perda of Samarinda City based on Government Regulation Number 6 Year 2010 about Pamoing Praja Police Unit Article 18 point d, can be given sanction that is dismissal. Keywords: Authority, Civil Service Police Unit, Local Regulation.